Marine Rhabdocoela (Platyhelminthes, Rhabditophora) from Uruguay, with the description of eight new species and two new genera - Van Steenkiste, N.; Volonterio, O.; Schockaert, E.; Artois, T. (Zootaxa, 2008)
An overview of the marine rhabdocoel fauna of Uruguay is given. Eight species, new to science, are described and discussed. Two of these, Acirrostylus poncedeleoni n.g. n.sp. and Polliculus cochlearis n.g. n.sp. could not be placed in any existing genera. A. poncedeleoni n.g. n.sp. can be recognized from other Cicerinidae Meixner, 1928 by the fact that there is only one ovovitellarium and by the lack of a cirrus in the male atrium. P. cochlearis n.g. n.sp. is characterized by the fact that there is only one testis and vas deferens, a unique situation within the Dalyelliidae Graff, 1905. Apart from these two species, six other new species are described: Cheliplana triductibus n.sp. and C. uruguayensis n.sp. (Karkinorhynchidae Meixner, 1928), Carcharodorhynchus viridis n.sp. (Schizorhynchidae Graff, 1905), Baicalellia forcipifera n.sp. (Provorticidae Beklemischew, 1928) and Vauclusia multistriata n.sp. and Coronhelmis mimosa n.sp. (Promesostomidae Den Hartog, 1964). All these species can be recognized from their congeners by the detailed structure of the genital organs in general, and the copulatory organ in particular. For four known species of Dalytyphloplanida Willems, 2006 new data are given: Ceratopera axi (Riedl, 1954) Den Hartog, 1964 (Trigonostomidae Graff, 1905), Lurus evelinae Marcus, 1950 (Luridae Sterrer & Rieger, 1990), Byrsophlebs caligulachaena (Ehlers & Ehlers, 1981) Karling, 1985 (Byrsophlebidae Graff, 1905) and Oneppus lacus Marcus, 1954 (Placorhynchidae Meixner, 1938). The occurrence of one new species of Polycystididae Graff, 1905 and the possible occurrence of Cheliplana firmata Brunet, 1968 and Proschizorhynchus atopus Marcus, 1950 are also mentioned.